2015
DOI: 10.1016/j.jmps.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anisotropic elasticity on the mechanical properties of fivefold twinned nanowires

Abstract: Previous atomistic simulations and experiments have shown an increased Young's modulus and yield strength of fivefold twinned (FT) face-centered cubic metal nanowires (NWs) when compared to single crystalline (SC) NWs of the same orientation. Here we report the results of atomistic simulations of SC and FT Ag, Al, Au, Cu and Ni NWs with diameters between 2 and 50 nm under tension and compression. The simulations show that the differences in Young's modulus between SC and FTNWs are correlated with the elastic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 76 publications
(7 reference statements)
2
46
1
Order By: Relevance
“…Apart from these fi ve TBs of the fi vefold twin, another four TBs (TB6, TB7, TB8, and TB9) intersecting with TB2 formed during the growth process and lots of steps and defects were thus located on TB2. Different from the disclination model, [ 28,37 ] the 7.5° misfi t was mostly shared by TB2 and TB4 thus broadening these two TBs, as shown in Figure 3 a. This was also confi rmed by the fast-Fouriertransform (FFT) image (inset in Figure 3 a), which showed that the spots of TB2 and TB4 were not as sharp as the ones of TB1, TB3, and TB5.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Apart from these fi ve TBs of the fi vefold twin, another four TBs (TB6, TB7, TB8, and TB9) intersecting with TB2 formed during the growth process and lots of steps and defects were thus located on TB2. Different from the disclination model, [ 28,37 ] the 7.5° misfi t was mostly shared by TB2 and TB4 thus broadening these two TBs, as shown in Figure 3 a. This was also confi rmed by the fast-Fouriertransform (FFT) image (inset in Figure 3 a), which showed that the spots of TB2 and TB4 were not as sharp as the ones of TB1, TB3, and TB5.…”
mentioning
confidence: 87%
“…Previous result have shown that the Schmid factor for the leading partial dislocation is a factor of two larger under tension than under compression, meaning that less stress is required to nucleate dislocations under tension compared to under compression. [ 28 ] Therefore, the stresses under compression are larger than those under tension, which has been proven in cyclic deformations. [ 51 ] So, the formation of full dislocations, which mainly nucleated from the steps on the twin boundaries, dominated the plastic deformation behavior, as was reported before.…”
mentioning
confidence: 97%
See 3 more Smart Citations